Analisis pengaruh persepsi terhadap safety riding pada masyarakat di sumbawa - Rafi'ah Rafi'ah; Iga Maliga; Asri Reni Handayani; Ana Lestari; Herni Hasifah (Jurnal Penelitian Pendidikan IPA, 2023)
Unsafe driving behavior can have several negative impacts on society. Motorcyclists who exhibit safe and law-abiding driving behaviors are essential in minimizing the risk of accidents on the road. Perception plays a crucial role in driving safety, as it allows individuals to interpret and comprehend information received through their senses. This ability is crucial in identifying potential hazards and making quick decisions to avoid accidents. This study aims to analyze the influence of perceptions on safe driving behavior. Additionally, it observes the driving behavior of motorcyclists between urban and rural areas in Sumbawa. The research adopts a quantitative approach with a comparative study design. The sample consists of 100 respondents selected through purposive sampling and divided into two regions. The statistical analysis using simple linear regression in SPSS version 16.0 shows a significance value of 0.04 with an 8.1% influence for perception on safe driving behavior. The T-test results for safety riding observations in urban and rural areas in Sumbawa indicate a T-test of 0.886. In conclusion, there is a significant but very weak influence between perception and safe driving behavior. The observation results show no difference in driving behavior between urban and rural areas in Sumbawa